Intellectual Capital Reporting in Malaysia - Too, Shaw Warn (INTI International University, 2009)
This research asserts to achieve two objectives. Firstly, it attempts to examine the extent and major categories of Intellectual Capital disclosure (ICD) in the Malaysian Initial Public Offerings (IPO) prospectuses. Secondly, it examines for the trend of ICD between year 2005 and 2006. Empirical tests are conducted on a sample size of 30 Malaysian companies seeking for listing in the Bursa Malaysia between year 2005 and 2006. The samples are selected from population which is stratified into year of listing. The extent of ICD is measured by "Disclosure Score Index" and content analysis is performed on the IPO of samples selected for year 2005 and 2006. The result of this research indicates a very low level of ICD among companies undergoing listing exercise. Among the three categories of ICD (i.e. external structure, internal structure and employee competence), external structure is the most reporting category. This result is consistent with the reporting practice in the annual report of listed corporations in Australia, Italy and Spain. In addition, there is a significant difference among the category of ICD. However, there has been no significant difference in the amount of reporting, by category and in total, from year 2005 to 2006 of the IPO prospectuses. The above results indicate a lack of awareness on the importance of ICD among business corporations in Malaysia. As the economy is getting more competitive and complex, the importance of disclosure of ICD, needs to be acknowledged, in enhancing information for users' decision-making.